Geological Identification of Seismic Source at Opak Fault Based on Stratigraphic Sections of the Southern Mountains - Pandita, Hita; Sukartono, Sukartono; Isjudarto, Agustinus (Forum Geografi, 2016)
Earthquake is one of the unpredicted natural disasters on our earth. Despite of the absence of high-accuracy method to precisely predict the occurrence of earthquake, numerous studies have been carried out by seismologists to find it. One of the efforts to address the vulnerability of a region to earthquakes is by recognizing the type of rock as the source of the earthquake. Opak Fault is an active fault which was thought to be the source of earthquakes in Yogyakarta and adjacent areas. This study aimed to determine the seismic source types of rocks in Yogyakarta and adjacent areas. The methods were by measuring stratigraphic sections and the layer thickness in the western part of Southern Mountains. Field study was done in 6 (six) research sites. Results of stratigraphic measurement indicated the sedimentary rocks in the Southern Mountains was 3.823 km in thick, while the bedrock was more than 1.042 km in thick. Based on the result, the rock types as the seismic source were thought to originate from the continental crust rocks formed of granite and metamorphic complex.